Catalytic oxidation of polyethylene with oxygen in aqueous dispersion. Issue 2 (8th May 2012) - Zawadiak, Jan; Orlińska, Beata; Marek, Adam A.
Abstract The oxidative degradation of polyethylene in aqueous dispersion was studied. The influences of different parameters as well as additives on polyethylene oxidation were investigated. The products obtained in noncatalytic and catalyzed by transition metal salts oxidation processes were compared and characterized by the determination of acid number as well as by means of ICP‐OES, GPC analysis, and FTIR spectroscopy. The obtained results have shown that the catalytic processes using manganese(II) or cobalt(II) acetylacetonate proceeded with two to three times higher rate than process without catalysts. Moreover, the FTIR spectroscopy and GPC analysis confirmed similar properties of final product obtained both in noncatalytic and catalytic processes. Another advantage of this process is a very low content of catalyst in product ∼ 0.001–0.003% of metal used. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013